The exposures and health effects of benzene, toluene and naphthalene for Chinese chefs in multiple cooking styles of kitchens. (November 2021) - Huang, Lei; Cheng, Haonan; Ma, Shengtao; He, Ruoying; Gong, Jicheng; Li, Guiying; An, Taicheng
Highlights: Naphthalene is one of the main pollutants in three types kitchens. Benzene in grilling kitchens exceeds the maximum risk acceptable level. Naphthalene in all kitchens has a serious non-carcinogenic risk. We studied the metabolite concentration of pollutants in urine on health effect. The levels of oxidative stress in chefs are influenced by metabolites. Abstract: Commercial cooking has higher intensity and more severe instantaneous cooking pollution from volatile organic chemicals compared to home cooking, making health risk assessment of occupational exposure for chefs a priority. In this study, chefs from three cooking styles of kitchens, including steaming, frying, and grilling, were selected to investigate the external and internal exposures, health risks and effects of several typical aromatic hydrocarbons (benzene, toluene and naphthalene). Naphthalene was found to be the most concentrated contaminant in air samples among the different kitchens, while benzene had the lowest concentration. The concentration of toluene in frying kitchens was significantly higher than that in steaming kitchens. Air concentrations of toluene in frying kitchens, as well as benzene concentrations in grilling kitchens exceeded the standard level according to indoor air quality standard (GB/T18883-2002). Regarding the metabolites of pollutants in urine, the content of S-benzylmercapturic acids (S-BMA) for frying chefs was significantly higher than that for other cooking styles of chefs, which was consistent with the relatively higher air concentrations of toluene. There was a good correlation between internal and external exposure of the pollutants. The level of oxidative stress was influenced by 2-hydroxynaphthalene (2-OHN) and S-BMA, indicating the potential health risks of these occupational exposed chefs. This study indicates the need to improve the monitoring of typical aromatic hydrocarbons, as well as to investigate their potential health effects in large-scale groups, and improve the ventilation in kitchens.